(untitled) (Minerva, 2019)
Ursula K. Le Guin rewrites the legend of the establishment of Eneas in Italy in Lavinia (2008) from the point of view of the female protagonist of the novel. This article analyzes three aspects in which the new narrative approach comes into conflict with the Virgilian text: the recreation of the archaic religion of the peoples of the Latium region, the rationalization of the mythological apparatus, typical of epic poetry, and the direct criticism against the moral virtues of the warrior stratum.